Innovation in Establishing the Standard of Care in a Self-Regulated Profession - Steele, Lindsay (Geoscience Canada, 2017)
Under Law, professional geoscientists have a duty of care that they must adhere to when they carry out their activities. The question is, when a duty of care exists, what is the standard of care that is owed? Geoscience regulators in Canada and around the world are working with geoscientists to develop innovative solutions in establishing the standard of care that must be met. By clearly establishing what our expectations are concerning standard of care, we are setting common ideals and goals as a professional community. Both society, geoscientists and employers of geoscientists look to regulatory associations for guidance on professional practice, therefore regulators need to strive to support and educate their members by developing tools and resources that allow members to meet the standard of care expected of them. The paper describes innovative approaches being offered to assist members of Engineers and Geoscientists BC and is based on an oral presentation given by the author at the International Geology Congress in Cape Town South Africa in August 2016.